2023
DOI: 10.3389/fphys.2023.1116705
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus attenuates renovascular hypertension–induced aortic remodeling dose dependently: the oxidative stress role and Ang II/cyclophilin A/ERK1/2 signaling

Abstract: Introduction: The high levels of angiotensin II (Ang II) can modify the vascular tone, enhance vascular smooth muscle cells (VSMCs) proliferation and hypertrophy and increase the inflammatory cellular infiltration into the vessel wall. The old herbal nonpharmacological agent, Hibiscus (HS) sabdariffa L has multiple cardioprotective impacts; thus, we investigated the role of HS extract in amelioration of renovascular hypertension (RVH)-induced aortic remodeling.Materials and methods: Thirty-five rats (7/group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(71 reference statements)
1
1
0
Order By: Relevance
“…This experiment explored whether KA-8 and PG-7 could reverse the Ang II-induced increase in the level of ROS in HUVECs. As shown in Figure , the Ang II group showed a stronger fluorescence state than the Con group, which was consistent with previous findings . After treatment with KA-8 and PG-7, the intracellular fluorescence intensity decreased significantly and the PG-7 group had the best effect.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This experiment explored whether KA-8 and PG-7 could reverse the Ang II-induced increase in the level of ROS in HUVECs. As shown in Figure , the Ang II group showed a stronger fluorescence state than the Con group, which was consistent with previous findings . After treatment with KA-8 and PG-7, the intracellular fluorescence intensity decreased significantly and the PG-7 group had the best effect.…”
Section: Resultssupporting
confidence: 91%
“…As shown in Figure 2 , the Ang II group showed a stronger fluorescence state than the Con group, which was consistent with previous findings. 10 After treatment with KA-8 and PG-7, the intracellular fluorescence intensity decreased significantly and the PG-7 group had the best effect. The results showed that two peptides, especially PG-7, could inhibit the production of ROS induced by Ang II in HUVEC, thereby reducing the oxidative damage caused by ROS.…”
Section: Resultsmentioning
confidence: 90%